The Effectiveness of Education Using Video and Pocket Book on Knowledge of Mothers to Stunting About PMT - Suci, Minah; Kalsum, Umi; Siregar, Nursyahid (Rifa'Institute, 2023)
Introduction: Stunting is a condition where toddlers have a length or height that is less than their age. The problem faced during the COVID-19pandemic is the limited delivery of knowledge about PMT to mothers of toddlers. The use of print media only stimulates the sense of sight, while audio-visual media conveys information in an audio and visual way providing visual and auditory stimuli. Methods: A quasi-experimental study in the form of a simple pretest-posttest control group design Results and Discussion: The test results showed that there was a significant difference in mother's knowledge about PMT before and after giving information using video media and pocket book media with a P-value test of 0.000. Conclusion: The difference in knowledge of the video group compared to the pocket book group is that the mean difference in knowledge in the video group is greater than the pocket book group, which means that video media is more effective than pocket book media in increasing the knowledge of mothers of stunting toddlers about PMT